Analysis of the Moringa oleifera Seed Oil Extract on Insulin Level in Alloxan-Induced Diabetic Rat (Rattus norvegicus) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Moringa oleifera is a plant that can be used and grown intensively in several Southeast Asian countries. Thisstudy aims to determine the effect of Moringa oleifera seed oil extract on the levels of the insulin and bloodglucose levels of Rattus norvegicus induced by alloxan. This study used 30 female Wistar white rats inducedby alloxan. Rats were divided into 6 groups. Groups 3 to 6 were injected 100, 200, 300, 400 mg/kg BWextract of Moringa oleifera seed oil, respectively. Group 1 neither had alloxan induction nor treatment whilegroup 2 had been induced alloxan but no treatment. Data were analyzed using the Kruskal-Wallis test witha significance level of 0.05. The results showed that there was no effect of Moringa oleifera seed oil extracton insulin level (p value = 0.161). Conversely, there was an effect on blood glucose levels in alloxan-inducedRattus norvegicus (p value = 0.036).
Keywords: Diabetes mellitus, Moringa oleifera, Rattus norvegicus.